Strategic Brand Management in Emerging Markets: Consumer Perceptions of Brand Extensions - Ozretic-Dosen, Durdana; Brlic, Marta; Komarac, Tanja (Organizations and Markets in Emerging Economies, 2018)
The purpose of this paper is to examine consumers’ perceptions of the parent brand and their attitudes towards the brand extensions by exploratory researching the topic in the new context of one emerging European market. Theoretical part gives a comprehensive description and analysis of the main features of the brand extension strategy. The purpose of the primary research is to explore and understand Croatian consumers’ perceptions about the global parent brand (Coca-Cola) and their attitudes towards its extensions on the Croatian market. Research results support the assumption that managers should introduce brand extension when they are sure of the position of the parent brand and its former extensions in the consumers’ mind. As such, results corroborate previous findings, showing how it is necessary to know the existing level of brand affect, brand loyalty, and brand trust since they have different impacts on consumers’ perceptions of the brand extension. The main contribution of the paper stems from the replication and extension of the previous research in the new context (in terms of the level of the market development and consumer culture). Research findings add to the existing knowledge with insights and results from the new market (Croatia), and as such might help in increasing understanding of the brand extension phenomena in the field of the strategic brand management in emerging markets.